The Changing Importance of Factors Influencing Students’ Choice of Study Mode - Bailey, M.; Ifenthaler, Dirk; Gosper, M.; Kretzschmar, M.; Ware, C. (Kluwer Academic Publishers, 2015)
Despite the expansion of online and blended learning, as well as open education, until relatively recently little research has been undertaken on what motivates students to enrol in particular study modes at university level. This project contributes to recent scholarship in the field by exploring the reasons why humanities students choose to study through specific modes. The research was conducted between October 2013 and March 2014 administering three waves of data collection to over 700 students who were enrolled in humanities units being offered simultaneously through three different modes: on-campus, distance, and open and online. The findings suggest that students choose different enrolment modes based on factors such as personal, learning support, environment, advice and marketing, teaching and learning as well as logistics. However, the importance students ascribe to particular factors changes during their educational experience. This study found significant differences in the importance of factors between initial and subsequent choices of enrolment mode, suggesting that the ‘lived’ experience of students at university influences their perception of which factors are important.